Awareness of Lassa Fever in a Rural Community in South West Nigeria - Olayinka Ilesanmi; Bridget Omotoso; Faith Alele; Peter Adewuyi (Shahid Sadoughi University of Medical Sciences, 2015)
Background: Lassa fever is an acute, virulent viral haemorrhagic illness with high morbidity and mortality rates. Its awareness remain low in sub urban or rural community. This study was carried out to assess the awareness of Lassa fever of a rural community in the south western part of Nigeria. Methodology: A descriptive cross sectional study of 122 respondents prior to a sensitization seminar on Lassa fever was carried out at Ijebu - Owo, Owo in Ondo State. Interviewer guided questionnaire was used to collect information and analysed with SPSS version 21. Descriptive statistics were done and frequencies and proportions were used to summarize variables of interest. Association between socio-demographic characteristics and awareness were explored using chi square. Level of significance was set at 5%. Results: The mean age of the respondents was 54.5±19.2years. Of the 122 respondents, 50.8% were males, three out of four (73.8%) were married, and 87.7% had secondary education and below. Those who had previously heard about Lassa fever were 17.2%. In all 7(46.7%) who had tertiary education had previously heard about Lassa fever compared to 14(13.1%) respondents who had secondary education and below (p=0.001) Conclusion: The study showed that there was poor awareness of Lassa fever among members of the community. Thus efforts should be made to increase the awareness of the populace through health campaigns, and to reduce the spread of both the vector and the virus.